Rilievo Laser Scanner 3D per il restauro della Chiesa di Santa Maria Maggiore a Mirandola - Scaletti, Leandro; Gira, Carlo (Archeomatica, 2021)
Digital survey technologies and three-dimensional modeling for the design analysis of the reconstruction of the Mirandola Cathedral after the 2012 earthquake. Verification and resizing of the wooden trusses and of the new light vaults for the construction of the roofs, for the restoration of the structures resisted to the earthquake and for the structural consolidation.